SELF-CONTROL AS A KEY DETERMINANT OF IMPULSIVE BUYING AMONG ADOLESCENT GIRLS IN SURABAYA - Nuril Wahidah; Siti Nurfitria (Archetype : Jurnal Ilmiah Psikologi dan Terapan, 2026)
This study aims to examine the influence of body image and self-control on impulsive buying behavior among adolescent girls who use skincare products in Surabaya. Using a quantitative cross-sectional design, data were collected from 100 adolescent girls aged 15–19 years. The research employed standardized instruments: the Body Image Scale (Cash, 2002), the Self-Control Scale (Averill, 1973), and the Impulsive Buying Scale (Verplanken & Herabadi, 2001). The results showed that body image and self-control together significantly influence impulsive buying behavior (p < 0.05), with an R² value of 0.429. However, when examined separately, only self-control had a significant negative effect on impulsive buying , while body image did not show a significant effect. These findings indicate that higher self-control reduces the likelihood of impulsive skincare purchases, whereas body image alone does not determine such behavior. The study confirming the role of self-control as a key determinant of impulsive buying in adolescents, consistent with the self-regulation model. At the same time, it challenges the assumption that body image is always a major factor in consumption behavior. The results suggest that contextual influences such as peer pressure, social media, and online marketing may play a stronger role than body image in driving impulsive skincare consumption.